Study of Plate and Frame Heat Exchanger Performance : The Effects of Mass Flow Rate, Inlet Temperature and Type of Flow Againts The Overall Heat Transfer Coefficient - Iqbal Syaichurrozi; Afdwiyarni Metta Karina; Ahmad Imanuddin (Eksergi)
The purpose of this study is to know the effects of mass flow rate, inlet temperature and type of flow againts overall heat transfer coefficient (U). Heat exchanger used in this study was plate and frame type of TRIMGS 10. Mass flow rate of hot fluida was variated into 0.3 and 0.253 kg/s; mass flow rate of cold fluida was variated into 0.276 and 0.22 kg/s; inlet temperature of hot fluida was variated into 40, 45, 50 oC; type of flow was variated into co-current and counter current. The results show that the faster mass flow rate hot and cold fluida, the bigger overall heat transfer coefficient obtained. Also, the higher inlet temperature, the the bigger overall heat transfer coefficient obtained.  In this study, the biggest of U value was obtained with variable of inlet temperatur 50°C, mass flow rate of cold fluid 0.276 kg/s, mass flow rate of hot fluid 0.3 kg/s, which were 140.6532 W/m2°C using type of counter-current flow and 135.4576 W/m2°C using type of co-current flow. Type of counter-current flow gave more satisfactory result of U value than type of co-current flow